[Rezension von: Calaway, Jared C., 1980-, The Sabbath and the sanctuary : access to God in the Letter to the Hebrews and its priestly context] - Moore, Nicholas J. (The journal of theological studies, 2014)
The Letter to the Hebrews describes access to the divine predominantly in terms of Christ’s high-priestly sacrifice and mediation. How does this cultic motif, which is broadly cosmological and spatial, relate to the lesser rest and Sabbath motif, which functions in a primarily eschatological, temporal manner? Through careful examination of Old Testament priestly traditions and extensive comparison with the Songs of the Sabbath Sacrifice Jared Calaway argues that Hebrews equates the Sabbath and the sanctuary whilst transforming them into exclusively heavenly realities.